2021
DOI: 10.1073/pnas.2025522118
|View full text |Cite
|
Sign up to set email alerts
|

4E-BP2–dependent translation in parvalbumin neurons controls epileptic seizure threshold

Abstract: The mechanistic/mammalian target of rapamycin complex 1 (mTORC1) integrates multiple signals to regulate critical cellular processes such as mRNA translation, lipid biogenesis, and autophagy. Germline and somatic mutations in mTOR and genes upstream of mTORC1, such as PTEN, TSC1/2, AKT3, PIK3CA, and components of GATOR1 and KICSTOR complexes, are associated with various epileptic disorders. Increased mTORC1 activity is linked to the pathophysiology of epilepsy in both humans and animal models, and mTORC1 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…We found the expression and sensitivity of 4EBP1 to be low. It is also suggested that 4EBP2, not 4EBP1, controls mTORC1 signaling, at least in parvalbumin-positive neurons (Sharma et al, 2021). Although our results are largely consistent with prior studies, the differences may be due to methodological or cell-type differences.…”
Section: Limitations Of the Studysupporting
confidence: 90%
“…We found the expression and sensitivity of 4EBP1 to be low. It is also suggested that 4EBP2, not 4EBP1, controls mTORC1 signaling, at least in parvalbumin-positive neurons (Sharma et al, 2021). Although our results are largely consistent with prior studies, the differences may be due to methodological or cell-type differences.…”
Section: Limitations Of the Studysupporting
confidence: 90%
“…Furthermore, while our data underscore that many alterations can be rescued by c4E-BP1 CA expression, it should not be inferred that dysregulated 4E-BP1 activity alone causes seizures. A recent study showed that ablation of 4E-BP2, but not 4E-BP1, reduces the threshold to chemoconvulsant-induced seizures in mice, although neither resulted in spontaneous seizures (Sharma et al, 2021). Interestingly, the effects on seizure threshold were specific to 4E-BP2 deletion in parvalbumin inhibitory neurons and not in other inhibitory or excitatory neurons in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a tours de force employing 11 different mouse lines, Sharma and colleagues recently shed more light on molecular and cellular mediators of mTOR-related regulation of brain excitability. 5 They provided support for neuronal mTORC1 signaling as a driver of brain excitability while at the same time emphasizing the importance of neuronal subtype.…”
Section: Commentarymentioning
confidence: 96%